Plant-Based Nutrition: Exploring Health Benefits for Atherosclerosis, Chronic Diseases, and Metabolic Syndrome—A Comprehensive Review - De Moraes-Ferrari, G; Cid-Jofre, V (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Atherosclerosis, chronic non-communicable diseases, and metabolic syndrome are highly interconnected and collectively contribute to global health concerns that reduce life expectancy and quality of life. These conditions arise from multiple risk factors, including inflammation, insulin resistance, impaired blood lipid profile, endothelial dysfunction, and increased cardiovascular risk. Adopting a plant-based diet has gained popularity as a viable alternative to promote health and mitigate the incidence of, and risk factors associated with, these three health conditions. Understanding the potential benefits of a plant-based diet for human health is crucial, particularly in the face of the rising prevalence of chronic diseases like diabetes, hypertension, dyslipidemia, atherosclerosis, and cancer. Thus, this review focused on the plausible advantages of consuming a type of food pattern for the prevention and/or treatment of chronic diseases, emphasizing the dietary aspects that contribute to these conditions and the evidence supporting the benefits of a plant-based diet for human health. To facilitate a more in-depth analysis, we present separate evidence for each of these three concepts, acknowledging their intrinsic connection while providing a specific focus on each one. This review underscores the potential of a plant-based diet to target the underlying causes of these chronic diseases and enhance health outcomes for individuals and populations. © 2023 by the authors.